The Effect of Shatahvadi Asthapana Basti and Dhum Nasya in Augmentation of Labor - A Case Study (AYUSHDHARA, 2023)
Normal labor is a natural physiological process, wherein a woman experiences intense and often excruciating pain. Though labor is a natural process, it is not uncommon for it to deviate from the norm due to a variety of factors such as altered anatomy, physiology, and other unknown variables, resulting in an abnormal labor experience. Ayurveda offers a wealth of knowledge on Prasava Paricharya. Our Acharyas have mentioned several medicinal preparations that aid in achieving Sukhprasava. Here in this case, there was a delay in the process of labor. After prolonged period of 12 hours with no substantial progress in labor, so we augment the labor process by administration of Shatahvadi Asthapana Basti mentioned by Acharya Vagbhata and Dhum Nasya mentioned by Acharya Kashyapa. Case Description: A 26 years multigravida female patient came to OPD of Prasuti Tantra evum Stri Roga, RGGPG ayurvedic hospital Paprola on date 7th June 2023 with the complaint of amenorrhoea for 8 months 22days and labor pain with no history of leaking. Aim: To assess the efficacy of given treatment in terms of decreasing pain and/or duration of labor. Objective: To study the effect of Shatahvadi Asthapana Basti and Dhum Nasya in augmentation of labor. Outcome: On 8th June 2023 a full term alive healthy female child of weight 3.1kg at 5:00 am was delivered by NSVD. Conclusion: This case study shows that given intervention augmented labor process without any resulting complication.